Molecular characterization of mucinous ovarian tumours supports a stratified treatment approach with HER2 targeting in 19% of carcinomas. Issue 1 (17th December 2012) - Anglesio, Michael S; Kommoss, Stefan; Tolcher, Mary C; Clarke, Blaise; Galletta, Laura; Porter, Henry; Damaraju, Sambasivarao; Fereday, Sian; Winterhoff, Boris J; Kalloger, Steve E; Senz, Janine; Yang, Winnie; et al.
Abstract: Mucinous ovarian carcinomas (MCs) typically do not respond to current conventional therapy. We have previously demonstrated amplification of HER2 in 6 of 33 (18.2%) mucinous ovarian carcinomas (MCs) and presented anecdotal evidence of response with HER2‐targeted treatment in a small series of women with recurrent HER2 ‐amplified (HER2+) MC. Here, we explore HER2 amplification and KRAS mutation status in an independent cohort of 189 MCs and 199 mucinous borderline ovarian tumours (MBOTs) and their association to clinicopathological features. HER2 status was assessed by immunohistochemistry (IHC), FISH, and CISH, and interpreted per ASCO/CAP guidelines, with intratumoural heterogeneity assessment on full sections, where available. KRAS mutation testing was performed with Sanger sequencing. Stage and grade were associated with recurrence on both univariate and multivariate analysis ( p < 0.001). Assessment of HER2 status revealed overexpression/amplification of HER2 in 29/154 (18.8%) MCs and 11/176 (6.2%) MBOTs. There was excellent agreement between IHC, FISH, and CISH assessment of HER2 status (perfect concordance of HER2 0 or 1+ IHC with non‐amplified status, and 3+ IHC with amplified status). KRAS mutations were seen in 31/71 (43.6%) MCs and 26/33 (78.8%) MBOTs, and were near mutually exclusive of HER2 amplification. In the 189 MC cases, a total of 54 recurrences and 59 deaths (53 of progressive disease) were observed. Within MCs, either HER2 amplification/overexpression or KRAS mutation was associated with decreased likelihood of disease recurrence ( p = 0.019) or death ( p = 0.0041) when compared to cases with neither feature. Intratumoural heterogeneity was noted in 26% of HER2‐overexpressing cases. These data support the stratification of MCs for the testing of new treatments, with HER2‐targeted therapy as a viable option for HER2+ advanced or recurrent disease. Further research is required to delineate the molecular and clinical features of the ∼34% of MC cases with neither HER2 amplification nor KRAS mutations.